The Ethics of Middlemen Business within the Small Scale Palm Oil Production Chain - Ishak, Suraiya; Awang, Abd Hair; Hussain, Mohd Yusof; Che Omar, Ahmad Raflis; Lyndon, Novel; Othman, Abdullah Sanusi (GEOGRAFI, 2018)
Middlemen are often accused as unethical and oppressing the farmers. Nevertheless, they remain essential to the value chain of agriculture product. This article aims to examine the ethics of middlemen within the small-scale agriculture sector based on the Theory of Moral Sentiment. This study employs a semi structured interview method with four palm oil fruit entrepreneurs (FD) in Sabak Bernam, Selangor. The interviews are guided by semi-structured questions. The findings indicate that the middleman business possess the element of rational sympathy and benevolence prescribed by the Moral Sentiment Theory. The execution of moral sentiment found in two areas - the commercial and social services. The commercial services consist of normal business activities such as purchase of crude palm fruits (FFB), farm management, selling of farm materials and transportation. Although the activities are fee-based, the smallholders gain benefits from the offered services. On the other hand, the social services are delivered through the provision of easy financial aids in the form of cash advance and/or credit facilities for purchased of farm materials. The provision of financial aids reflects the benevolence of FD who willing to sacrifice the potential of creating an extra profit. The smallholders gain benefits through the cash advance because they are provided in the absence of collateral, non-compliance of rigid loan application procedures and finance charges. Furthermore, the payback of the loan is flexible and taking into consideration the financial situation of the smallholders. Therefore, we conclude that FD business within this context is parallel with the requirement of moral sentiment.